Real-time monitoring of the sialic acid biosynthesis pathway by NMR. Issue 13 (15th March 2023) - Gorenflos López, Jacob L.; Schmieder, Peter; Kemnitz-Hassanin, Kristin; Asikoglu, Hatice Ceyda; Celik, Arif; Stieger, Christian E.; Fiedler, Dorothea; Hinderlich, Stephan; Hackenberger, Christian P. R.
Abstract : From chemical shifts to conversion velocity: real-time NMR spectroscopy using a combination of 1D and 2D experiments can monitor individual enzymatic steps in the sialic acid biosynthesis pathway in rat liver cytosolic extract. Abstract : Sialic acids are part of the outermost component of the glycocalyx of all vertebrates; as such, they are fundamental markers in physiological and pathological processes. In this study, we introduce a real-time assay to monitor individual enzymatic steps of sialic acid biosynthesis, either with recombinant enzymes, in particular using UDP- N -acetylglucosamine 2-epimerase (GNE) or N -acetylmannosamine kinase (MNK), or in cytosolic rat liver extract. Using state-of-the-art NMR techniques, we are able to follow the characteristic signal of the N -acetyl methyl group, which displays different chemical shifts for the biosynthesis intermediates UDP- N -acetylglucosamine, N -acetylmannosamine (and its 6-phosphate) and N -acetylneuraminic acid (and its 9-phosphate). Pseudo 2- and 3-D NMR demonstrated that in rat liver cytosolic extract, the phosphorylation reaction of MNK is exclusive for N -acetylmannosamine generated by GNE. Thus, we speculate that phosphorylation of this sugar from other sources ( e.g. external application to cells) or N -acetylmannosamine derivatives often applied in metabolic glycoengineering is not conducted by MNK but by a yet unknown sugar kinase. Competition experiments with the most prevalent neutral carbohydrates demonstrated that of these, only N -acetylglucosamine slowed N -acetylmannosamine phosphorylation kinetics, suggesting an N -acetylglucosamine-preferring kinase as the acting enzyme.